(untitled) - Sakaiya, Taichi (Tokyo, 1991)
Soar with Sakaiya on a dizzying journey with this prophetic view of the future. His latest work (he has written 30 books) has already sold over 500,000 copies in Japan and should be successful in this English edition. Sakaiya easily transcends other works in this genre, such as Alvin Toffler's The Third Wave ( LJ 4/1/80) or Daniel Bell's The Coming of Post-Industrial Society ( LJ 7/73), as he describes a future knowledge-value society. Knowledge-value is "the price of and the value created by wisdom, and the worth, or price a society gives to that wisdom." Massive changes will characterize this brave new world, and Sakaiya describes the three main "disrupters" as technological advances, population shifts, and dwindling resources. His review of history and broad-brushed approach without footnotes may frustrate some. This is sure to be in demand by CEOs and futurist thinkers and is strongly recommended for most libraries.
Keywords: Dự báo xã hội,Công nghệ và văn minh,Xã hội thông tin,Social prediction,Technology and civilization,Information society